2018
DOI: 10.1093/annweh/wxy018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Workplace Exposure and Stress on Neck Pain and Disabilities in Women—A Longitudinal Follow-up After a Rehabilitation Intervention

Abstract: High perceived stress and low 'control of decision' were associated with more neck pain, increased neck disability, and decreased work productivity. Treatment interventions for individuals with neck pain should take into account psychosocial workplace exposures and stress to improve intermediate and long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Psychosocial work environment factors such as job strain, control, demands, and perceived stress were also reported to be associated with decreased productivity and work ability (Martimo et al 2009). Furthermore, a recent study by Svedmark et al (2018) showed associations between stress and decreased productivity. People with reduced working capacity more often report high work-related stress.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Psychosocial work environment factors such as job strain, control, demands, and perceived stress were also reported to be associated with decreased productivity and work ability (Martimo et al 2009). Furthermore, a recent study by Svedmark et al (2018) showed associations between stress and decreased productivity. People with reduced working capacity more often report high work-related stress.…”
Section: Discussionmentioning
confidence: 98%
“…It has also been presented through two work-related questions that measure productivity loss due to pain or discomfort in terms of quality and quantity of work. These questions were presented in 2009 by Martimo et al (2009), and were recently applied to study associations between neck pain and productivity (Svedmark et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is established that neck pain is associated with psychological distress, including stress, depression and anxiety (Blozik et al., 2009; Elklit & Jones, 2006; Sterling et al., 2005; Svedmark et al., 2018; Wenzel, Haug, Mykletun, & Dahl, 2002). In the general population, these factors have been shown to be associated with raised inflammatory markers (Hansel et al., 2010; Naude, Roest, Stein, de Jonge, & Doornbos, 2018; Tayefi et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…stress, depression, smoking, low physical activity, obesity and poor diet; Galland, 2010; Hansel, Hong, Camara, & von Kanel, 2010; McFarlin et al., 2006; Sproston & Ashworth, 2018; Tayefi et al., 2017). These factors are commonly present in people with musculoskeletal pain (Blozik et al., 2009; Nilsen, Holtermann, & Mork, 2011; Sterling, Jull, Vicenzino, Kenardy, & Darnell, 2005; Svedmark, Bjorklund, Hager, Sommar, & Wahlstrom, 2018; Vandenkerkhof, Macdonald, Jones, Power, & Macfarlane, 2011; Zvolensky, McMillan, Gonzalez, & Asmundson, 2010), with some potentially having a causal effect (Mauck et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While the correlation between depression, perceived injustice, and opioid use in chronic pain is well established, there is little knowledge about the possibly contributing socioeconomic factors. High perceived stress, e.g., due to high job demands and low control of decisions at work, was associated with more neck pain and decreased work productivity [16][17][18][19]. Occupational factors can also have a significant influence on the development of low back pain disorders [20].…”
Section: Introductionmentioning
confidence: 99%